Klasifikasi Metode Kebahasaan dalam Ushul Fiqh - Wahyuni, Sri; Yusuf, Enjang Burhanuddin (TSAQOFAH, 2025)
The primary sources of Islamic law revealed by Allah SWT through the Qur’an and Hadith were delivered in Arabic, reflecting the historical and linguistic context of the Prophet Muhammad’s (SAW) mission in the Arabian Peninsula. However, not all Muslims, particularly mujtahids, possess native-level Arabic proficiency, thereby necessitating precise linguistic methodologies for interpreting legal texts. This study aims to identify and classify linguistic methods within usul al-fiqh through a literature review employing a descriptive content analysis approach. The findings illustrate a range of linguistic approaches used to derive legal meanings from shar'i texts, including the method of Dilālah an-Nash (such as ‘Ibarah an-Nash, Isyarah an-Nash, Iqtidha’ an-Nash), the classification of wadlih ad-dilālah (explicit meanings) such as dzāhir, nash, mufassar, muhkam, and ghair wadlih ad-dilālah (ambiguous meanings) such as khafī, musykil, mujmal, and mutasyābih. The study also explores the concept of mafhum (including mafhum mukhalafah and mafhum muwafaqah), as well as lexical analysis concerning generality and specificity (‘āmm–khāṣ), unrestricted and restricted meanings (mutlaq–muqayyad), commands and prohibitions (amr–nahy), and semantic interpretation based on word usage (ḥaqīqah–majāz, ṣarīḥ–kināyah). The study concludes that the comprehension of Islamic law necessitates a systematic linguistic methodology to interpret shar'i texts accurately and contextually, especially for non-Arabic speakers.